Promoting classroom inclusion for children with disabilities in rural South India - Jeff Boniface; Dinesh Krishna; Marie Brien; Ramasubramanian Ponnusamy; Navamani Venkatachalapathy; Donna Drynan (Social Sciences and Humanities Open)
Purpose: This study explored teachers' perception of the current state of classroom inclusion for children with disabilities in rural South India. Identification of facilitators and barriers to classroom inclusion, through consultation with teachers, informed the development of a school inclusion awareness program. Methods: This qualitative study utilized semi-structured focus groups with teachers at public and private schools in rural South India. Thematic analysis and interpretive description were applied to analyze responses and situate results within the context of rural South India. Results: A total of 18 teachers participated in three focus groups. Three common themes emerged from the data: 1) Perceptions of disability impact inclusion; 2) Individualized education as a strategy for inclusive education and 3) Differing needs for inclusive education training. Conclusion: Findings suggest that current societal attitudes and education systems in India are inherently exclusionary to children with disabilities. Teacher-reported perceptions and experiences provide valuable insights for the development of a school awareness program addressing various types of disabilities, as well as inclusive education training targeted at evidence-based individualized education strategies.